Already have an account? Get multiple benefits of using own account!
Login in your account..!
Remember me
Don't have an account? Create your account in less than a minutes,
Forgot password? how can I recover my password now!
Enter right registered email to receive password!
Given f ( x ) = 2 + 3x - x2 and g ( x ) = 2 x -1 evaluate ( f + g ) ( 4)
Solution
Through evaluate we mean one of two things based on what is in the parenthesis. If there is a number in the parenthesis then we desire a number. If there is an x (or no parenthesis, as that implies & x) then we will carry out the operation and simplify as much as possible.
( f + g ) ( 4) = f ( 4) + g ( 4)
= (2 + 3( 4) - 42 ) + (2 + 4( -1)
= -2 + 7
= 5
6[5b+9]=2b+9.
Example: Sketch the graph of ellipses. (x +2) 2 /9 + ( y - 4) 2 /25 =1 Solution So, the center of this ellipse is ( -2, 4) and as usua
how to find the eliminate of 4x+2y=2 and x-5y=-16?
answer in scientific notation correct to the ten thousandths 471,598,000,000
Solve out the following system of equations by using augmented matrices. 3x - 3 y - 6 z = -3 2x - 2 y - 4 z = -2 -2x + 3 y + z = 7 Solution Notice that this system
"I wish these guys would stop fighting and be a little more accommodating of each other's point of view," thought TomHoffmeyer, Vice President of Marketing at the General Mills Com
f(x)=x^2+6x-38
turn into an inequality expression, y= (0,330) x= (110,0)
#2t+rh=2
what is the square root of 169
Get guaranteed satisfaction & time on delivery in every assignment order you paid with us! We ensure premium quality solution document along with free turntin report!
whatsapp: +1-415-670-9521
Phone: +1-415-670-9521
Email: [email protected]
All rights reserved! Copyrights ©2019-2020 ExpertsMind IT Educational Pvt Ltd